Study on Relationship between Calcium and Iron and Dietary Life - Kato, Eiko; Tomioka, Takashi; Seki, Chiyoko; Kimira, Mitsuru; Iwase, Yasuhiko; Akabane, Masayuki (Eiyōgaku zasshi, 1991)
Relationship between the dietary life and calcium and iron intake was studied on 185 female junior college students living primarily in metropolitan Tokyo. Following results were obtained. 1) Calcium and iron intake (78.1% and 78.2%) was lower than RDA. 2) Various food intake was analysed by classifying them into three groups; (less than 60%), (60-90%), (more than 90% of RDA); that of legumes, green and yellow vegetables, other vegetables, fish, meat and eggs with iron intake (p<0.05). 3) A questionnaire survey revealed that many students of the high calcium group (more than 90% of RDA) drank much milk, and that those of the high iron group had good appetites, were careful to take more number of food items compared to the other group, and came from multiple generation families.